SISTEM PENDUKUNG KEPUTUSAN CALON PENERIMA RASKIN DENGAN METODE POLYGONS AREA METHOD (PAM) DI KELURAHAN AIRNONA-KOTA KUPANG - Reza S Baliara; Dony M Sihotang; Arfan Y Mauko (J-Icon : Jurnal Komputer dan Informatika, 2018)
Raskin (Beras Miskin) is one of the Indonesian government programs to help reduce the expenditure of the poor people. This program is conducted by Bulog and Local Government. Raskin distribution procedure at Airnona sub-district is still using manual method, that those who will receive Raskin is submitted by RT, so that a Decision Support System (DSS) is needed to help handle the problem. The PAM (Polygons Area Method) method is one of the methods in DSS which can help solve unstructured problems. This study uses 8 criteria namely, monthly income, quantity of dependents, floor area of the house, the type of house floor, type of the house wall, assets, lighting source, and drinking water source. System test is done by comparing the ranking system with the name issued by Dinas Sosial. This test uses 66 interview data with 2016 recipient data resulting in similarity rate of 43% and unsimilarity rate is 57%. During then analysis on several data the conclusion is system able to provide good result.